Pemanfaatan PowerPoint dalam Canva pada Pembelajaran Pendidikan Agama Islam di MI Abdurrahman Kota Bandung - Destiawati Destiawati; Muhammad Pauji Aripin; Iqlima Mutiara Alifah; Muhamad Wahyudin; Az-Zahra Putri Maulida; Hani Hadiyati Pujawardani (Tarbiatuna: Journal of Islamic Education Studies, 2024)
One of the many technology applications that are present in the world of education can be used as learning media in the scope of education is Canva, in the media program there are various graphic designs such as presentations, graphics, posters, and so on. The Canva application can be used through a device or PC. A qualitative approach in research by matching empirical reality with applicable theory using descriptive methods. The qualitative approach also uses research procedures that produce descriptive data in the form of written or spoken words from the behavior of the people observed. As for its implementation in the utilization and use of canva at MI Abdurrahman, it has the aim that students can make presentations and have confidence, where the curriculum currently used has a vision to create education that is more flexible, relevant, and in favor of the needs of students.